2017
DOI: 10.1016/j.lungcan.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of survival in young patients with small cell lung cancer: Results from the California Cancer Registry

Abstract: A B S T R A C TBackground: Small cell lung cancer (SCLC) is an often lethal disease that commonly occurs in older individuals with a history of heavy tobacco use. Limited epidemiologic and outcomes data are available on young SCLC patients aged less than 50 years of age. We assessed clinical variables related to cause specific survival (CSS) of young patients with SCLC. Methods: SCLC patients in the California Cancer Registry diagnosed between 1998 and 2012 were included. Primary outcome measure was CSS. Hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…Twenty-two studies reported hazard ratios on the association between an area-based SES index measure and lung cancer survival ( 5 , 6 , 22 , 37 , 63 , 70 , 72 74 , 79 , 81 83 , 86 , 91 94 , 101 , 105 107 , 116 ) (Table S4 ). Group comparisons of 18 studies ( 5 , 22 , 37 , 63 , 70 , 72 , 74 , 79 , 81 , 82 , 86 , 91 94 , 101 , 105 107 ) showed significant associations between lower income areas and a lower survival after lung cancer diagnosis in 10 studies ( 5 , 22 , 37 , 70 , 79 , 82 , 92 , 93 , 101 , 106 ), with a range of HR 1.05–2.21 (Figure 5 ). Nine studies ( 5 , 22 , 74 , 79 , 91 93 , 105 , 107 ) adjusted for stage at diagnosis (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two studies reported hazard ratios on the association between an area-based SES index measure and lung cancer survival ( 5 , 6 , 22 , 37 , 63 , 70 , 72 74 , 79 , 81 83 , 86 , 91 94 , 101 , 105 107 , 116 ) (Table S4 ). Group comparisons of 18 studies ( 5 , 22 , 37 , 63 , 70 , 72 , 74 , 79 , 81 , 82 , 86 , 91 94 , 101 , 105 107 ) showed significant associations between lower income areas and a lower survival after lung cancer diagnosis in 10 studies ( 5 , 22 , 37 , 70 , 79 , 82 , 92 , 93 , 101 , 106 ), with a range of HR 1.05–2.21 (Figure 5 ). Nine studies ( 5 , 22 , 74 , 79 , 91 93 , 105 , 107 ) adjusted for stage at diagnosis (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data sources for cancer survival were usually national cancer registries but also cohort studies and clinical trials ( 50 , 53 ). Most studies reported on all types of lung cancer, but 20 studies restricted analyses to non-small-cell lung cancer (NSCLC) patients ( 5 , 34 , 44 , 45 , 50 , 56 , 63 , 66 , 68 , 72 , 76 , 80 , 88 90 , 93 , 96 , 97 , 101 , 112 , 115 ) and three studies were restricted to small-cell lung cancer (SCLC) patients ( 6 , 92 , 114 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other lung neoplasms, SCLC commonly occurred in older individuals with a smoking history . Younger adults with SCLC have been described to account for a very small proportion and are underrepresented in clinical trials . Older patients with SCLC always faced hormonal decline, immune response deterioration and comorbidities which may delay the beginning of treatment and limit treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering adolescents' malignancies were treated in children's hospital in China, we defined the young‐onset patients in the 18‐39 age range. Limited by the proportion of young patients, only a few studies have addressed whether patients with SCLC under 40 years have distinct characteristics and the prognostic factors have been rarely studied . Additionally, although young patients with SCLC are a small population, considerable attention should be given considering their remaining expected lifespan, financial productivity and roles in caring for their families …”
Section: Introductionmentioning
confidence: 99%
“…Demographics, histology and pathological staging are among clinical indicators that have been proven in the literature [34][35][36], hence previous works on predicting survival among NSCLC patients are concentrated on mixing these readily available clinical factors with AUCs range between 0.62-0.79 [19][20][27][28]. To the best of our knowledge, this is the first study establishing the fusion of both clinical with imaging covariates, which has been proven to better predict survival (AUCs between 0.77 and 0.97).…”
Section: Discussionmentioning
confidence: 99%